US national cybersecurity international politics, concepts and organization - Van Puyvelde, Damien; Brantly, Aaron Franklin (Routledge studies in conflict, security and technology, 2017)
This volume explores the contemporary challenges to US national cybersecurity. Related to these themes, this volume pinpoints three pressing challenges US decision makers and their allies currently face as they attempt to govern cyberspace: maintaining international order, solving conceptual puzzles to harness the modern information environment, and coordinating the efforts of diverse partners.